TAHLIL AL-AKHTHA 'INDA MUTA'ALLIMI AL-LUGHAH AL-'ARABIYAH LI AL-NAATHIQIINA BI GHAIRIHA - Khalid Khamis Farraj (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
This study is aimed to analyze spelling error of Arabic for non Arabic native in Institute of Islamic and Arabic Sciences (LIPIA), Indonesia. This study also contributes in developing curriculum of Arabic studies. The sample of this study is 117 students of Syaria Faculty who study in the first semester. They have learnt at Arabic preparation program for two years before. The spelling error which is analyzed include language style and grammar. The procedures of analysis include (1) error identification of Arabic spelling, (2) error description of Arabic spelling, (3) identification of error repetition number and (4) data analysis and findings’ interpretation.DOI: 10.15408/a.v2i1.1517